2013
DOI: 10.1007/s11682-013-9221-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of changes in brain structure and cognitive functions in adult stem cell transplant recipients

Abstract: Hematopoietic stem cell transplantation (HSCT) is an efficacious treatment for many hematologic malignancies. However, the conditioning regimen of high-dose (HD) chemotherapy with or without total body irradiation (TBI) can be associated with neurotoxicity. In this prospective study, we used quantitative neuroimaging techniques to examine regional gray matter and ventricular volumes, and standardized neuropsychological tests to assess cognitive function before and one year after HSCT in twenty-eight patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…Chemotherapy has previously been associated with cognitive and structural brain changes in many cancer survivors and could therefore appear to be a contributing factor to the identified deficits in this study (Simo et al 2013). However, most of the previous chemotherapy-related studies performed in long-term breast cancer survivors found subtle cognitive deficits and structural brain changes predominantly in frontal regions (Correa et al 2013;Deprez et al 2011;Inagaki et al 2007;McDonald et al 2013). Indeed, our research group also conducted a neuropsychological and neuroimaging study on SCLC patients following a platinum-based chemotherapy prior to PCI.…”
Section: Discussionmentioning
confidence: 55%
“…Chemotherapy has previously been associated with cognitive and structural brain changes in many cancer survivors and could therefore appear to be a contributing factor to the identified deficits in this study (Simo et al 2013). However, most of the previous chemotherapy-related studies performed in long-term breast cancer survivors found subtle cognitive deficits and structural brain changes predominantly in frontal regions (Correa et al 2013;Deprez et al 2011;Inagaki et al 2007;McDonald et al 2013). Indeed, our research group also conducted a neuropsychological and neuroimaging study on SCLC patients following a platinum-based chemotherapy prior to PCI.…”
Section: Discussionmentioning
confidence: 55%
“…Our analysis demonstrated evidence of abnormalities in nodal degree, nodal clustering coefficient, or nodal betweeness centrality in certain hubs including superior frontal gyrus, middle frontal gyrus, superior parietal gyrus, precuneus, supplementary motor area, and calcarine. Some of these hub areas have been reported to be associated with TBI outcomes based on structural or functional neuroimaging findings [Correa et al, 2013; Kohl et al, 2009; Leunissen et al, 2013; Lipszyc et al, 2014; Max et al, 2006; Sanchez-Carrion et al, 2008; Scheibel et al, 2007; Tuner and Levine, 2008; Wilde et al, 2012]. For example, the superior parietal gyrus was found to have significant changes in cortical thickness [Wilde et al, 2012] and functional activation [Kohl et al, 2009] in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…112 They noted grey matter loss and a concomitant increase in ventricular volume in patients 1-year following HCT, and no corresponding changes in healthy participants in the control group. Despite the noted changes in neuroimaging, statistically significant differences in rates of neurocognitive dysfunction were not found.…”
Section: Correlatesmentioning
confidence: 94%